ANALISIS LOKASI DAN KERAGAMAN FASILITAS DALAM MENINGKATKAN DAYA TARIK BERKUNJUNG WISATAWAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) PANTAI BATU HODA (BATU HODA BEACH) DI SAMOSIR - Naibaho, Rizal; Sihombing, Marlon (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
The tourism sector is one of the largest contributors to regional income in Samosir district. Therefore, researchers conducted research at one of the most popular tourist attractions for tourists in Samosir district, namely Batu Hoda Beach. The purpose of this study was to analyze the location factor and the diversity of facilities in increasing the attractiveness of visiting tourists at the Batu Hoda Beach Samosir tourist attraction. This form of research is descriptive research with a qualitative approach. Researchers describe the results of the analysis of the two factors, namely location and diversity of facilities and the consequences that occur. Researchers emphasize research instruments on humans contained in the object of research which are used as informants in this study. This type of research is descriptive research with a qualitative approach. This research seeks to describe the results of the analysis with the consequences that occur. This is based on the consideration that researchers want to understand the location factor and the diversity of facilities in increasing the attractiveness of visiting tourists at micro, small and medium enterprises (MSMEs) at Batu Hoda Beach (Batu Hoda Beach) Samosir. The research results are summarized through 3 (three) stages of data collection techniques, namely interviews, observations, and literature studies. Furthermore, the data obtained in the field is then re-examined and described. From the results of data processing, the researcher summarizes the things that have been focused on to be presented and arranged systematically. Furthermore, researchers conducted a data verification stage by making conclusions based on the data obtained from the research results.